Teaching strategies of the teacher in the Pe Innovation Classroom dagogical (AIP) and learning of primary school students in educational institutions in the district of Villa María del Triunfo. Lime. 2014 - Berrospi Torres, Beatriz (2019)
Today is present in Peru, a reduction in the average student / computer ratio from 71 in 2000 to 7 in 2015, To this is added the rise of various international organizations that propose teaching skills for the present century in the technological aspect . This context of new teaching scenarios and performances motivated the realization of the present non-experimental quantitative descriptive study, in order to determine the level of basic technological competences in sixty classroom teachers of pedagogical innovation of the Educational Institutions of the district of Villa María del Triunfo, from your own perspective. Methodologically, the survey technique was used based on the application of a questionnaire previously validated by expert judgment and subjected to the internal consistency test of Cronbach's Alpha (0.981). In addition, the instrument considered a total of 55 items distributed in six dimensions. Among the results obtained, it stands out that 43.33; 48.33 and 50.00% of the teachers surveyed are located at the advanced level corresponding to the knowledge dimensions of basic technology, work with basic computer applications and Internet activities, respectively. However, the frequency in this advanced level is reduced to 28.33; 41.67 and 23.33% of teachers for the management of educational software, activity with multimedia applications and management of multimedia presentations, respectively. The latter results in 41.67; 36.67 and 51.67% of the teachers are located in the basic level of technological competences for the aforementioned dimensions.